2022
DOI: 10.1093/ehjcvp/pvac001
|View full text |Cite
|
Sign up to set email alerts
|

SGLT-2 inhibitors and cardiovascular outcomes in patients with and without a history of heart failure: a systematic review and meta-analysis

Abstract: Aims Sodium-glucose co-transporter 2 (SGLT-2) inhibitors have cardiovascular (CV) benefits in patients with heart failure with reduced ejection fraction (HFrEF). Whether these medications improve CV outcomes irrespective of heart failure history or left ventricular ejection fraction (LVEF) in HFrEF remains unknown. Methods and Results All randomized, placebo-controlled trials of SGLT-2 inhibitors reporting similar CV outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Finally, SGLT2i have also showed a marked reduction in the progression in CKD in patients with or without type 2 diabetes (CREDANCE with canagliflozin, 22 DAPA‐CKD with dapagliflozin 10 and SCORED with sotagliflozin 23 and EMPA‐KIDNEY with empagliflozin 24 ). These landmark RCTs showed the pleiotropic benefits of SGLT2i 25 resulting in licensing authorizations in those with type 2 diabetes, heart failure with reduced ejection fraction and CKD. The results of our study further support the ubiquitous mortality and cardiovascular benefits of SGLT2i therapy in people with type 2 diabetes through showing these effects in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, SGLT2i have also showed a marked reduction in the progression in CKD in patients with or without type 2 diabetes (CREDANCE with canagliflozin, 22 DAPA‐CKD with dapagliflozin 10 and SCORED with sotagliflozin 23 and EMPA‐KIDNEY with empagliflozin 24 ). These landmark RCTs showed the pleiotropic benefits of SGLT2i 25 resulting in licensing authorizations in those with type 2 diabetes, heart failure with reduced ejection fraction and CKD. The results of our study further support the ubiquitous mortality and cardiovascular benefits of SGLT2i therapy in people with type 2 diabetes through showing these effects in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several GLP-1 agonists have already been shown to reduce adverse cardiovascular outcomes among diabetics ( Sheahan et al, 2020 ). SGLT2i, such as Empagliflozin ( Anker et al, 2021 ) and Dapagliflozin ( McMurray et al, 2019 ), bestow favorable cardiovascular effects, regardless of the patients’ diabetic status ( McMurray et al, 2019 ; Anker et al, 2021 ; Razuk, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SGLT-2i have been approved for heart failure patients with reduced ejection fraction (HFrEF) even if they do not have diabetes [ 30 ]. Perhaps one of the most important benefits of using SGLT-2i is its cardiac benefits, including the reduction of major cardiovascular events, hospitalization rates due to heart failure, and death.…”
Section: Reviewmentioning
confidence: 99%